Networking strategy for entrepreneurship education in the IES - Ana María Holguín Montoya (Universidad del Magdalena, 2014)
In order to strengthen the processes of entrepreneurship developed in different institutions of higher education and improving the entrepreneurial model of the city of Medellín, institutions like the Mayor's Office and COMFAMA (Family Benefit Institution), unite to add economic efforts and management in order to lead the program called City E. The overall objective of the program is to establish measures aimed at improving skills and abilities in the different actors of entrepreneurship in higher education institutions of the IES city. Unify criteria and that the capacity on issues related to entrepreneurship and the creation of productive and competitive enterprises. To this end, the Bolivarian Pontifical University makes tracing models of entrepreneurship in HEIs nationally and internationally and designed and implemented from the results of research conducted by the UPB a curriculum model and comprehensive support for the creation companies.